Analisis Kesalahan dan Kendala Siswa/i SMA Citra Harapan Percut dalam Menyelesaikan Sistem Persamaan Linear Dua Variabel (SPLDV) serta Solusi Pembelajarannya - Kairuddin Kairuddin; Naftali Marbun; Renata Siburian; Jona Mikhael Hutagaol; Artorito Sitorus; Reva Lenita Girsang; Mirna Wulan Sari Sianipar (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to explore in depth the errors and obstacles experienced by students in learning the System of Linear Equations in Two Variables (SLSV), and to provide strategic solutions to improve their understanding and skills. SLSV is a fundamental topic that is very important for developing logical and analytical thinking skills. However, various studies show that students, especially at the vocational high school level, still face significant challenges, particularly when converting story problems into mathematical models, formulating strategies, and being thorough in completing the process. This study applies a qualitative descriptive method involving 25 students from grade X of SMK Swasta Citra Harapan located in Deli Serdang Regency. Primary data were collected through written tests (pre-test and post-test) and interviews with mathematics teachers. The findings of this study indicate that students' initial understanding of SLSV is still minimal, as reflected in the low percentage of correct answers in the pre-test (Problem 1: 32%; Problem 2: 48%). The most frequent errors made by students include the inability to convert story problems into mathematical models, errors in the elimination or substitution process, and errors in algebraic operations. The proposed approach is to implement integrated learning strategies, including Problem-Based Learning (PBL) to reinforce concepts, the use of interactive media to provide motivation, and the habit of systematically recording steps through the Think Talk Write (TTW) approach to improve procedural skills and the accuracy of answers. This study concludes that successful mastery of SPLDV requires a comprehensive strategy that combines conceptual, procedural, and motivational aspects.